Effects of Polysaccharide from Chuanminshen violaceum on Immune Response of Newcastle Disease Vaccine in Chicken - Xu Song (Acta Scientiae Veterinariae, 2013)
Background: Newcastle disease (ND), caused by avian paramyxovirus serotype 1 (APMV-1), also known as Newcastle disease virus (NDV), is regarded as one of the two most devastating diseases of poultry with the characteristics of serious disease and high fl ock mortality. It causes severe economic losses in domestic poultry, especially in chickens. At present, there were no effective drugs to treat this disease and the main method to control ND was vaccination. Moreover, new strains of virus resistant to chemotherapy continue to emerge, so does the need for a safe and effective vaccine. The immune adjuvant can make vaccine generate a strong immune response providing long-term protection against infection. With commonly usage of some immune adjuvants (e.g. mineral oil and aluminium hydroxide), many problems were occurred, such as side effects, strong local stimulation and carcinogenesis, together with complicated preparation, or failure to increase immunogenicity of weak antigen and so on. Botanical polysaccharides, as a new type of adjuvant or immunopotentiator, had become the hot research area because of their less side effects and no toxicity. The purpose of this research was to observe whether Chuanminshen violaceum polysaccharide (CVPS) possessed synergistical immunoenhancement, and offer the theoretical evidence for developing potential new-type adjuvant. Materials, Methods & Results: 200 three-yellow chickens at one day of age were randomly divided into four groups and reared in separated pens. On 7 days old, the average maternal serum hemaglutination inhibition (HI) antibody titer was less than 3 log2, all chickens of each group (the average body weight (BW) was 120 g) were vaccinated with ND live vaccine through nasal drip and eye-drop. At the same time, the chickens in three CVPS groups (high, medium and low doses of CVPS) were orally administered with 0.5 mL of CVPS at concentrations of 100 mg/kg BW, 50 mg/kg BW, 25 mg/kg BW respectively, once a day for fi ve successive day, in negative control group (NC), with 0.5 mL of physiological saline, once a day for fi ve successive day. On days 14, 21 and 28, the serum antibody titer, erythrocyte-C3b receptor rosette rate (E-C3bRR), erythrocyte-C3b immune complex rosette rate (E-ICRR), peripheral lymphocyte proliferation and peripheral CD4+/CD8+ ratio were measured. The results showed that the antibody titer, E-C3bRR, elimination rate of immune complex and peripheral lymphocyte proliferation in three CVPS groups and peripheral CD4+/CD8+ ratio in medium dosage of CVPS group were signifi cantly higher (P < 0.05) than those in control group throughout the process of whole experiment almost. Discussion: The CVPS not only improved the E-C3bRR and accelerated the elimination rate of CIC, but also induced higher antibody titer, peripheral lymphocyte proliferation and peripheral CD4+ /CD8+ ratio in chickens vaccinated against ND live vaccine. This indicated that CVPS possessed immune-enhancement effi cacy